Family Agathotanaidae Lang, 1971a* - Larsen, Kim (Zootaxa, 2007)
The family Agathotanaidae was represented in the trench material by one new species of Agathotanais, A. hadalis; one new species of Paragathotanais, P. abyssorum and one previously described species of Paranarthrura. The new species are described and both genders of P. vitjazi Kudinova-Pasternak, 1970 are re-described. Paranarthrura zevinae Kudinova-Pasternak, 1970 is transferred to Paragathotanais.